2014
DOI: 10.4236/jbise.2014.76039
|View full text |Cite
|
Sign up to set email alerts
|

Chaos-Based Encryption of ECG Signals: Experimental Results

Abstract: In this work, we suggest a system for chaos-based encryption of electrocardiographic signals. It uses simple electronics organized around a colpitts chaotic oscillator. The system has been designed, implemented and tested. The encrypted signal has been decrypted and compared to the original ECG signal. Experimental results were analysed and proved encouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…We recall equations governing the Colpitts system [33] {1em4ptx˙y˙z˙1em4pt===1em4ptσfalse(1+efalse(y1false)false)γfalse(1+efalse(y1false)false)ρfalse(x+yfalse)λz1em4pt++1em4ptχzμzThis system is solved numerically using the fourth‐order Runge–Kutta method with integration step Δ t = 10 −3 and initial values false(x0,y0,z0false) = (0.4, 0.1, 0.1). The values taken by the elements of the quintuplet ( σ , χ , γ , μ , ρ ) determine the nature of the solution of the system.…”
Section: Presentation Of the Chaotic Mapsmentioning
confidence: 99%
“…We recall equations governing the Colpitts system [33] {1em4ptx˙y˙z˙1em4pt===1em4ptσfalse(1+efalse(y1false)false)γfalse(1+efalse(y1false)false)ρfalse(x+yfalse)λz1em4pt++1em4ptχzμzThis system is solved numerically using the fourth‐order Runge–Kutta method with integration step Δ t = 10 −3 and initial values false(x0,y0,z0false) = (0.4, 0.1, 0.1). The values taken by the elements of the quintuplet ( σ , χ , γ , μ , ρ ) determine the nature of the solution of the system.…”
Section: Presentation Of the Chaotic Mapsmentioning
confidence: 99%
“…For each oscillator, one series is positive, the second one nil, and the third one negative. ese prove the chaotic nature of the oscillators [17].…”
Section: Duffing Oscillatormentioning
confidence: 81%
“…In our generated sequences, we have chosen a new technique to quantify the quality of the chaos. A comparative study was conducted on several traditional techniques such as MLE, Shannon entropy, and permutation entropy [17][18][19][20][21][22][23][24], but this study revealed that they were all time consuming and therefore less suitable for real-time systems [25]. A new algorithm was developed, the PLSE (permutation large slope entropy).…”
Section: Introductionmentioning
confidence: 99%